Implementation science: A critical but undervalued part of the healthcare innovation ecosystem - Sze Ling Chan; Elaine Lum; Marcus E. H. Ong; Nicholas Graves (Wiley, 2022)
Abstract Healthcare systems face many competing demands and insufficient resources. Service innovations to improve efficiency are important to address this challenge. Innovations can range from new pharmaceuticals, alternate models of care, novel devices, and the use other technologies. Suboptimal implementation can mean lost benefits. This review article aims to highlight the role of implementation science, summarize how settings have leveraged this methodology to promote translation of innovation into practice, and describe our own experience of embedding implementation science into an academic medical center in Singapore. Implementation science offers a range of methods to promote systematic uptake of research findings about innovations and is gaining recognition worldwide as an important discipline for health services researchers. Health systems around the world have tried to promote implementation research in their settings by establishing (1) dedicated centers/programs, (2) offering funding, and (3) building knowledge and capacity among staff. Implementation science is a critical piece in the translational pathway of "evidence to innovation." The three efforts we describe should be strengthened to integrate implementation science into the innovation ecosystem around the world.